2018
DOI: 10.1136/inp.k2584
|View full text |Cite
|
Sign up to set email alerts
|

Assessing quality of life and welfare of donkeys in the UK

Abstract: The role of donkeys in the UK and Europe has changed over the past 40 years, and is still changing – these equids are primarily used as companions, but also for tourism, therapy and increasingly for milk production. When it comes to the end of their lives and issues surrounding equine end-of-life care, a recent study highlighted that many donkey owners rely on their vet to provide them with information on quality of life (QOL) assessment, geriatric care and euthanasia planning. This article aims to assist vete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Poor QOL was identified as one of the main issues affecting the horse at the time of euthanasia (42.6%). Several studies of euthanasia in equids also identified QOL as an important factor 17,18 . It was therefore unsurprising that for over 90% of participants, compromise to the current or future QOL of their horse was a ‘very important’ factor that influenced their decision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor QOL was identified as one of the main issues affecting the horse at the time of euthanasia (42.6%). Several studies of euthanasia in equids also identified QOL as an important factor 17,18 . It was therefore unsurprising that for over 90% of participants, compromise to the current or future QOL of their horse was a ‘very important’ factor that influenced their decision.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of euthanasia in equids also identified QOL as an important factor. 17,18 It was therefore unsurprising that for over 90% of participants, compromise to the current or future QOL of their horse was a 'very important' factor that influenced their decision. This was a similar finding of another study, although their focus was specifically on euthanasia decisions for aged horses.…”
Section: Discussionmentioning
confidence: 99%
“…In severe cases, muscle wastage develops particularly in the shoulder region. Unfortunately, severe changes are seen frequently in geriatric donkeys particularly when changes occur gradually over time and a reduced quality of life is not recognised (Thiemann et al., 2018).…”
Section: Diagnosismentioning
confidence: 99%
“…Body weight, feed ingestion and blood metabolic parameters measurements are important to evaluate donkey health [ 9 ] and productive performance. Furthermore, fewer investigations have focused on the physiological phases [ 10 , 11 ] and diet in dairy jennies compared to other livestock species, and to the best of our knowledge no reference values are available for biochemical parameters in pregnancy and lactation.…”
Section: Introductionmentioning
confidence: 99%